2022
DOI: 10.3390/ijerph19084435
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Tobacco Treatment Training Program

Abstract: There is a need for program evaluations associated with educating healthcare professionals about the treatment of patients who use tobacco. The purpose of this study was to evaluate a Tobacco Treatment Specialist Training program with a pre-test and post-test (provided six months after the program) to determine if participants-maintained knowledge and practices to help patients with tobacco cessation in a mixed-model analysis. A pre-test survey was administered to attendees of a three-day tobacco treatment tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Despite this, however, the percentage of standalone substance use treatment centers that mandated screenings was similar to that of other health care settings. This suggests that such mandates are possible in all health care settings, including the least resourced ones, though there may be a need for greater (or more frequently refreshed) support provision in these settings (e.g., more training, Certified Tobacco Treatment Specialists, TUA templates [ 84 , 85 ]) relative to others to address the myriad perceived barriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, however, the percentage of standalone substance use treatment centers that mandated screenings was similar to that of other health care settings. This suggests that such mandates are possible in all health care settings, including the least resourced ones, though there may be a need for greater (or more frequently refreshed) support provision in these settings (e.g., more training, Certified Tobacco Treatment Specialists, TUA templates [ 84 , 85 ]) relative to others to address the myriad perceived barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, until there is more work, the value of key practices that were not significantly or independently associated with mandated screenings should not be discounted as unimportant. Additionally, and although these were not the specific focus of this study, tobacco-free workplace policies have been found to help reduce tobacco use by enhancing physical cues in treatment center environments to facilitate a quit attempt; likewise, the presence of Certified Tobacco Treatment Specialists has been linked with evidence-based intervention provision [ 84 , 85 , 86 , 97 ]. Unfortunately, tobacco-free workplace policy implementation was reported at (marginally significant) lower rates in substance use treatment centers, both those in LMHAs and standalone centers, compared with the other types of surveyed centers, revealing a need to intervene to increase their uptake in these settings.…”
Section: Discussionmentioning
confidence: 99%
“…Second, greater attention to staff training and practice facilitation is likely needed to increase organizational readiness and support local champions to adopt best practices for tobacco treatment throughout diverse cancer care settings. In addition to traditional delivery channels of continuing medical education and TTS training programs, 31,32…”
Section: Discussionmentioning
confidence: 99%
“…Second, greater attention to staff training and practice facilitation is likely needed to increase organizational readiness and support local champions to adopt best practices for tobacco treatment throughout diverse cancer care settings. In addition to traditional delivery channels of continuing medical education and TTS training programs, 31,32 the establishment of learning collaboratives 33 or communities of practice would accelerate the implementation of clinical practice guidelines for tobacco treatment and could be tailored to the local context and available resources. In Just ASK, participating programs readily volunteered to share solutions and effective models of care during webinars, suggesting the feasibility of this evidence-based implementation strategy for practice innovation and the value of shared problem-solving.…”
Section: Discussionmentioning
confidence: 99%